The law and economics of orderly and effective insolvency - Crawford, Keith (2013)
What is effective insolvency law? Effective insolvency laws play an important role in the health of an economy, and particularly upon the framework of investment decisions. Understanding how this works is particularly relevant during a period of financial crisis. International Monetary Fund and World Bank guidelines for “Orderly and Effective” insolvency laws were intended to encourage law reforms that would stimulate investment by improving returns to investors in the event of insolvency. The guidelines were strongly influenced by an efficiency approach to insolvency. This approach posits that absolute priority for secured creditors is allocatively efficient and therefore the best means to achieve maximum social welfare. The guidelines also drew heavily on the principles and practices of ‘creditor friendly’ English law, seen by some as a paragon of efficient insolvency. But how accurate is this appraisal of English law or the impact of efficient insolvency?